Efeito da suplementação alimentar no comportamento de bugios-ruivos (Alouatta guariba clamitans) - Back, Janaína Paula (2018)
Research on the influence of food supplementation on primate behavior has focused on terrestrial and semiterrestrial species. Its effects on highly arboreal primates are poorly known. We assessed whether and how food supplementation affects the feeding behavior and activity budget of two howler monkey groups (JA and RO) inhabiting periurban forest fragments in southern Brazil. The behavior of the three adult members of each group were observed via focal-animal method for six to eight full days (dawn to dusk) per month from March to August 2017 (916 h of observation). The feeding events of the focal-individual of the day were recorded using the “all occurrences” method. The activity budget of the adults of both groups, considering a full day (24 h), was dominated by resting (84%-89%), followed by feeding (9%-5%), moving (6%-4%) and social behavior (both 1%). The supplementation was unevenly distributed during the day and accounted for 6% of all feeding events in both groups. JA always received fruit in a platform, whereas RO had access to fruits and processed foods on roofs and directly from humans. The mean (± sd) ingested biomass of wild foods by each adult howler (g/day) was ca. 300% higher than the ingested biomass of supplemented foods (JA: 406 ± 176 vs 116 ± 97; RO: 364 ± 229 vs 113 ± 108). However, the ingestion rate (g/min) of supplemented foods was >300% higher than that of wild foods (JA: 17 ± 20 vs 4 ± 4; RO: 20 ± 29 vs 6 ± 8). The supplementation reduced the ingestion of wild fruits, but not the consumption of leaves. The ingested biomass of supplemented foods was a good predictor of moving time in RO and social interactions in JA. In sum, food supplementation partially changed the selection of wild foods by howlers and increased their frequency of affiliative behaviors.